SYNTHESIS OF 3-(2-PYRIDYL)-N-METHYL-1,2,4-TRIAZOLES AND THEIR COORDINATION COMPOUNDS WITH PD(II): UDC 546.98+547.792+543.429.23 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
Alkylation of 3-(2-pyridyl)-1,2,4-triazole with iodomethane leads to formation of 3-(2-pyridyl)-N1-methyl-1,2,4-triazole (L1) and 3-(2-pyridyl)-N2-1,2,4-triazole (L2), which were used for synthesis of palladium(II) complexes PdL1Cl2 and PdL2Cl2. The composition and structure of obtained compounds were proposed on the basis of IR and 1H NMR spectroscopy data and elemental analysis. IR spectra of synthesized ligands have a lot in common, due to their structure similarity. In the IR spectrum of ligands L1 and L2 we observe intense CH band of triazole fragment in the 3000 cm-1, bands of valence and deformation vibrations of CH of pyridine ring in the 1200-1600 cm-1. As a result of coordination all signals in the IR spectra are shifted. Complexes PdL1Cl2 and PdL2Cl2 have mononuclear structure. PdL1Cl2 partially dissociate in solution of DMSO, it is detected by means of 1H NMR spectra in which we observe signals of ligands protons. It is could be due to structural features of formed coordination compound.1H NMR spectra of obtained ligands is bit similar, this is due to their structure. Signals of pyridine ring protons 3-(2-pyridyl)-N1-methyl-1,2,4-trazol shifted to 0.11-0.12 ppm in a weak field in compare with 3-(2-pyridyl)-N2-methyl-1,2,4-triazol. Signals of protons in the 5th position L1 are shifted in a strong field compared to L2. N1-CH3 signals are shifted to weaker field than N2-CH3, it can be explained by the influence of negative magnetic anisotropy of pyridine ring.Coordination of all ligands occurs through the nitrogen atom of pyridine ring and N4-triazole. In this case all L1 and L2 signals of pyridine  protons suffer shift to a weak field (L1: Δδ = 0,28 ... 0,36; L2: Δδ = 0,27 ... 0,38). Triazole proton is shifted to 0.36 ppm for Pd(L1)Cl2 and 0.63 for Pd(L2)Cl2 in compare with uncoordinated ligands.
Keywords: 1,2,4-triazole, palladium(II), IR spectroscopy, NMR spectroscopy